answersLogoWhite

0


Best Answer

x2 + 6x + 1 = 0

x2 + 6x + 9 = 8

(x + 3)2 = 8

x + 3 = ± 2√2

x + 3 = -3 ± 2√2

x ∈ {-3 - 2√2, -3 + 2√2}

User Avatar

Wiki User

โˆ™ 2010-02-25 05:47:09
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: X2 plus 6x plus 1 equals 0?
Write your answer...
Submit
Related questions

X2 plus 6x plus 9 equals 81?

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)


X2 plus 6x-40 equals 0?

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10


What is -x2 plus 6x plus 7 equals 0?

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}


Factor x2-6x plus 5 equals 0?

(x - 3)(x - 2)


What are the roots of x2 plus 6x plus 12 equals 0?

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3


X squared plus 6x plus 8 equals 0?

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4


X2 plus 6x plus 6 equals 0?

No answer in integers. Quadratic formula gives roots as -1.268 and -4.732


X2 plus 6x-2 equals 0?

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13


Put the equation x2 plus 3x plus 7 equals 6x plus 18 in the form ax2 plus bx plus c equals 0?

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0


What are the roots of the quadratic equation x2 - 6x plus 8 equals 0?

x = 2 and x = 4


What conic section does the equation x2 4y2 6x 8y plus 1 equals 0 represent?

hyperbola


What is x2 plus 6x plus 5 equals 0?

Factors are (x + 5)(x + 1) so x = -5 or -1


What is x2 plus 6x plus 9 equals x plus 3?

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2


X2 plus 6x-72 equals 0?

(x + 12)(x - 6) = 0 x = 6 or -12


X2 plus 6x plus 9 equals 49?

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4


X2 plus 6x-110 equals 0?

x2 + 6x - 110 = 0 ∴ x2 + 6x = 110 ∴ x2 + 6x + 36 = 146 ∴ (x + 6)2 = 146 ∴ x + 6 = ±1461/2 ∴ x = -6 ±1461/2 ∴ x ≈ 6.083, 18.083


If x2 plus 6x equals 27 what is the value of x?

x2 +6x = 27 x2 + 6x - 27 = 0 x2 + 9x - 3x - 27 = 0 x(x + 9) - 3(x + 9) =0 (x - 3)(x + 9) = 0 So x can equal 3 or -9.


What are the solutions for the quadratic equation x2 plus 6x equals 16?

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.


What is 3x squared plus 6x-3 equals 8 in the form of Ax squared plus Bx plus C equals 0?

It is: 3x2+6x-11 = 0


How do you solve x2 - 6x - 13 equals 14?

If: x2-6x-13 = 14 Then: x2-6x-27 = 0 And: (x+3)(x-9) = 0 So: x = -3 or x = 9


What is x2 minus 6x plus 5 equals 0?

(x-5)(x-6) so x=5,6


X2 - 6x equals -8?

This is a quadratic equation question in finding the possible values of x x2 - 6x = - 8 x2 - 6x + 8 = 0 Factorise the expression in the equation: (x-2)(x-4) = 0 Therefore: x = 2 or x = 4


What are the roots of the following equation x2 plus 6x plus 2 equals 9?

x^2+6x+2=9 x^2+6x-7=0 (x+7)(x-1)=0 x=-6,1 for your roots


Find the value or values of x in the quadratic equation x2 equals 6x-9?

In the equation x2 = 6x - 9, all terms must be moved to one side of the equals sign, giving x2 - 6x + 9 = 0. This becomes factorable to (x -3)(x-3).


Find the center and radius of the circle with this equation X2 plus Y2 minus 6X plus 2Y equals 0?

The centre is (3,-1) and the radius is sqrt(10).

Study guides

๐Ÿ““
Create a Study Guide